A Comparative Study of Oocyte Quality Between Hypothyroid and Non-Hypothyroid Patients Undergoing Fertility Treatment - Rajendra Shitole, Janhvee Patidar, Dimple Desai,Pawan Kulkarni, Sayali Chavan (South Eastern European Journal of Public Health, 2025)
Background: Oocyte quality can be influenced by various factors, including hypothyroidism. This study aimed to compare the oocyte quality between hypothyroid and non-hypothyroid patients undergoing fertility treatments. The study was conducted as a retrospective analytical investigation at DPU in vitro fertilization (IVF) & Endoscopy Centre, Pimpri, Pune. Method: This retrospective cohort study assessed the oocyte quality of hypothyroid and non-hypothyroid women with diminished ovarian reserve (diminished ovarian reserve (DOR)), polycystic ovarian disease (polycystic ovarian disease (PCOD)), endometriosis, and unexplained infertility who were undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment. Clinical data from 400 patients were analyzed, with 182 selected for evaluation. Among these, 50% (n=91) had hypothyroidism, and the other 50% (n=91) did not. Results: The comparative study of oocyte quality showed no statistically significant differences between hypothyroid and non-hypothyroid groups in terms of total retrieved oocytes or quality categories (A: Good, B: Fair, C: Poor). Subgroup analyses of unexplained infertility (p=0.346), diminished ovarian reserve (DOR) (p=0.718), endometriosis (p=0.167), and polycystic ovarian disease (PCOD) (p=0.68) also showed no significant differences in oocyte quality between the groups. Conclusion: Women with hypothyroidism who underwent in vitro fertilization (IVF) were more likely to produce fewer oocytes and exhibit greater oocyte dysmorphism compared to non-hypothyroid women. However, these differences were not statistically significant Categories: Obstetrics/Gynaecology, Infertility, Public health,